Salvage sequential integrated boost radiotherapy followed by sintilimab–bevacizumab in cervical small-cell carcinoma with >10 brain metastases: A 3-year survivor case report - Xu, Yuanyuan; Gong, Xiang; He, Huailin; Deng, Xiangyu; Zhang, Zhenhua; Wen, Qinglian; Li, Dan (Frontiers in Immunology, 2025)
BackgroundCervical small cell carcinoma (CSCC) is a rare and highly aggressive malignancy with a poor prognosis. Brain metastases develop in 10–20% of patients, complicating clinical management and underscoring the need for effective therapeutic strategies.Case presentationA 54-year-old female with CSCC developed 16 isolated brain metastases during treatment. She responded markedly to whole-brain radiotherapy (WBRT) combined with sequential integrated boost radiotherapy (SEB). Although recurrence emerged outside the SEB field one year later, subsequent treatment with immune checkpoint inhibitors and antiangiogenic agents induced complete remission (CR), achieving a progression-free survival (PFS) of 16 months. Remarkably, the patient has achieved an overall survival of 3 years since the diagnosis of brain metastases, without significant treatment-related cognitive impairment, and remains in CR.ConclusionThe combination of WBRT and SEB improves metastatic dose coverage in CSCC patients with multiple brain metastases. Furthermore, combining immunotherapy with antiangiogenic therapy demonstrates significant efficacy against post-radiation intracranial recurrence, supporting a multimodal individualized approach for further study.